2022
DOI: 10.3389/fmicb.2022.914868
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity of Thymol Against Drug-Resistant Streptococcus iniae and Its Protective Effect on Channel Catfish (Ictalurus punctatus)

Abstract: Streptococcus iniae is a zoonotic pathogen, which seriously threatens aquaculture and human health worldwide. Antibiotics are the preferred way to treat S. iniae infection. However, the unreasonable use of antibiotics leads to the enhancement of bacterial resistance, which is not conducive to the prevention and treatment of this disease. Therefore, it is urgent to find new efficient and environmentally friendly antibacterial agents to replace traditional antibiotics. In this study, the antibacterial activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 73 publications
0
9
1
Order By: Relevance
“…Therefore, the mode of action of this compound to F. tricinctum was investigated. It was found that the cell wall structure of F. tricinctum was not or only slightly affected by the treatment of thymol, which is in contrast to a recent study claiming that thymol could damage the cell wall of the bacterium Streptococcus iniae 43 . This may be resulted from the distinct difference of cell wall structure between fungi and bacteria.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Therefore, the mode of action of this compound to F. tricinctum was investigated. It was found that the cell wall structure of F. tricinctum was not or only slightly affected by the treatment of thymol, which is in contrast to a recent study claiming that thymol could damage the cell wall of the bacterium Streptococcus iniae 43 . This may be resulted from the distinct difference of cell wall structure between fungi and bacteria.…”
Section: Discussioncontrasting
confidence: 72%
“…It was found that the cell wall structure of F. tricinctum was not or only slightly affected by the treatment of thymol, which is in contrast to a recent study claiming that thymol could damage the cell wall of the bacterium Streptococcus iniae. 43 This may be resulted from the distinct difference of cell wall structure between fungi and bacteria. However, thymol could rapidly cause the damage of plasma membrane and increase membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Thymol is involved in the up-regulation of genes coding for outer membrane protein synthesis. It also interacts with membrane proteins which disrupt outer and inner membrane and intracellular targets 42,43 . Carvacrol is responsible for the inhibition of flagellin which damages bacterial motility 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Thymol enhances anti-oxidative capacity to alleviate OS in different tissues [ 33 ]. As a spectrum anti-bacterial agent, thymol reduces the activities of microorganisms belonging to the Enterobacteriaceae, Streptococcus, and Saccharomycetaceae families, involving membrane rupture, inhibition of biofilm formation, and other pathways [ 34 , 35 ]. Thymol shows anti-viral potential to inhibit virus colonization, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-298), by docking with the S1 receptor-binding domain of spike glycoprotein [ 36 ].…”
Section: Pharmacokinetics and Pharmacological Properties Of Thymolmentioning
confidence: 99%